Tomato early blight biocontrol and plant growth promotion by Clonostachys spp. - Rodrigues Junior, Orlando Maciel (2019)
Given that fungal biocontrol agents not only suppress diseases, but also confer benefits for plants, this work aimed to evaluate the effect of different Clonostachys species against tomato early blight and on plant growth and biomass accumulation. Regarding biocontrol, we hypothesized that non-pathogenic, epiphytic isolates of Cladosporium added to leaf surfaces could act as a living support for the mycoparasitic Clonostachys spp. in a combined application scheme, enhancing the biocontrol effects. We also hypothesized that extending the Clonostachys application after the Alternaria linariae inoculation might provide a ‘curative’ effect on diseased plants. First, isolates of five Clonostachys species were sprayed alone or in combination with a mix of four Cladosporium spp. isolates twice before pathogen inoculation. No marked evidence was found to support the benefit of combined application of these BCA’s. In the second assay, preventive spraying with single isolates of three Clonostachys species resulted in in more than 50% reduction in disease intensity, reaching a maximum of 72% with C. chloroleuca isolate UCBV 12. Additional post-inoculation spray did not result in enhanced biocontrol efficacy or detectable curative effects. In a distinct set of experiments, 21 isolates from nine different Clonostachys species, plus two isolates of Beauveria and Trichoderma, were tested for growth promotion of tomato seedlings after either single-step seed microbiolization or seed microbiolization followed by biodrenching of saturated conidial suspensions after seedling emergence. Tomato seedlings were evaluated for length and dry matter. Single-step seed microbiolization was inefficient in viproviding benefits. Contrastingly, clear plant growth promotion effects were detected after biodrenching. Seven isolates from five Clonostachys species consistently resulted in significant plant mass increases ranging from 21% to 33%, the latter result obtained with the isolate UCBV 35 of C. byssicola. Clonostachys isolates probably were able to colonize rhizosphere due to more efficient form of conidial delivery through drenching, a practice that can be easily adopted in tomato seedling production. Plant growth promotion seems to be another common feature of Clonostachys genus, just as the mycoparasitism ability.